A method to improve the performance of carbon-based perovskite solar cells

By regulating the defect state density of carbon nanotubes and doping them into HTL, the HTL/graphene electrode interface of carbon-based perovskite solar cells is optimized, and the problem of low efficiency of carbon-based perovskite solar cells is solved, and the problem of low efficiency of carbon-based perovskite solar cells is achieved. High efficiency and stable battery performance.

CN114447235BActive Publication Date: 2025-02-18DALIAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210093639.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-26
Publication Date
2025-02-18
Estimated Expiration
2042-01-26

AI Technical Summary

Technical Problem

The photoelectric conversion efficiency of carbon-based perovskite solar cells is lower than that of metal-based PSCs, mainly due to the energy level barrier between the carbon material/HTL interface, poor interface contact and low carrier mobility of organic HTL.

Method used

By regulating the defect state density of carbon nanotubes, optimizing their electrical characteristics, and doping them into organic p-type semiconductors to prepare HTL, improving the energy level arrangement and interface contact between HTL/graphene electrodes.

Benefits of technology

The photoelectric conversion efficiency of carbon-based perovskite solar cells is significantly improved, increasing it to more than 22%, and maintaining a battery efficiency of more than 95% after continuous light for 800 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114447235B_ABST
    Figure CN114447235B_ABST
Patent Text Reader

Abstract

The present invention belongs to the fields of new material technology and new energy technology, and provides a method for improving the performance of carbon-based perovskite solar cells, specifically, a hole transport material prepared by mixing defect-controlled carbon nanotubes with organic p-type semiconductors is spin-coated on the surface of the perovskite layer, and then a carbon electrode is deposited to assemble the carbon-based perovskite solar cell. In the present invention, the carrier transport characteristics are regulated by controlling the defect state density of the carbon nanotubes, the surface roughness, work function and carrier mobility of the film are improved by adjusting the content of the carbon nanotubes in the hole transport layer, the interface contact and energy level matching between the hole transport layer and the carbon electrode are optimized, and the photoelectric conversion efficiency of the carbon-based perovskite solar cell is improved, and the preparation method is simple, the stability is high, the cost is low, and the universality is excellent. The present invention can promote the practical application of carbon-based perovskite solar cells, accelerate the industrialization process of perovskite solar cells, and has important practical value and economic value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the fields of new material technology and new energy technology, and specifically relates to a method for improving the performance of carbon-based perovskite solar cells. Background Art

[0002] In recent years, perovskite solar cells (PSCs) have attracted widespread attention due to their excellent optoelectronic properties. The photoelectric conversion efficiency (PCE) has significantly increased to 25.5% in the past decade. The device structure is FTO / electron transport layer / perovskite / hole transport layer / metal Ag or Au. However, the corrosion characteristics of halide ions in perovskites on Ag / Au metal electrodes seriously restrict their commercialization. In contrast, carbon-based perovskite solar cells (C-PSCs) with carbon materials as electrodes show better environmental tolerance to heat, moisture and oxygen than metal electrodes.

[0003] Carbon materials have poor carrier separation and hole selectivity. If carbon directly contacts perovskite, it will cause huge energy loss. Therefore, the hole transport layer (HTL) is an essential material for efficient C-PSC. Although carbon-based perovskite solar cells have made major breakthroughs, and the highest reported C-PSC photoelectric conversion efficiency (PCE) has been increased to 19.2%, it is still far lower than that of metal-based PSCs. The main problems are as follows: First, the energy level barrier at the carbon material / HTL interface causes serious energy loss; second, the different surface morphologies of HTL and carbon materials make their surface roughness differ by two orders of magnitude, resulting in poor interface contact and gaps. These interface gaps become carrier recombination centers and lead to slow charge extraction; third, the low carrier mobility of organic HTL increases the risk of carrier recombination. There have been studies on increasing the hole mobility of HTL by doping. For example, Chong Chen et al. applied CNT doped with spiro-OMeTAD HTL modified with TiO2 nanoparticles to PSCs based on gold electrodes in the article entitled "Multifunctional CNT: TiO2 additives in spiro-OMeTAD layer for highly efficient and stable perovskite solar cells". Another example is Henry J. Snaith et al.'s article entitled "Carbon Nanotube / Polymer Composites as a Highly Stable Hole Collection Layer in Perovskite Solar Cells". P3HT functionalized CNTs were embedded in PMMA as HTL for PSCs based on silver electrodes to enhance hydrophobicity and stability. However, all related work was applied to PSC devices with metal electrodes. In addition, for carbon-based electrode devices, Kerttu Aitola et al. reported in an article titled "High Temperature-Stable Perovskite Solar Cell Based on Low-Cost Carbon Nanotube Hole Contact" and Kerttu Aitola et al. reported the use of single-walled CNTs as both hybrid HTL and as counter electrodes for charge collection in an article titled "Carbon nanotube-based hybrid hole-transporting material and selective contact for high efficiency perovskite solar cells".However, since the carbon layer in the above C-PSC device structure needs to reach a certain thickness to ensure the required conductivity, this is accompanied by a large increase in non-radiative carrier recombination defects. Therefore, the regulation of the electrical properties of carbon materials, carbon / HTL interface matching, and appropriate device structure are the key to improving the efficiency and stability of C-PSC, which has important theoretical significance and practical value for the commercial application of PSC. Summary of the invention

[0004] The purpose of the present invention is to provide a method for improving the performance of carbon-based perovskite solar cells. The preparation method of the present invention can obtain a carbon-based perovskite solar cell with low cost, good stability and high photoelectric conversion efficiency.

[0005] In order to achieve the above-mentioned invention object, the present invention adopts the following technical solutions:

[0006] (1) dispersing carbon nanotubes in a mixed solution of concentrated nitric acid and concentrated sulfuric acid at a volume ratio of 1:0.5-5 with a concentration of 98 wt.%, then ultrasonically treating at 25-60° C. for 1-12 hours, repeatedly washing the dispersion with deionized water until it is neutral, and drying the obtained solid under vacuum conditions for 24-48 hours to obtain a carbon nanotube powder with controlled defect state density;

[0007] (2) dispersing carbon nanotube powder in chlorobenzene or other solvents at a concentration of 0.01 to 0.1 g / L, and ball milling for 10 to 24 hours to obtain a small-sized uniformly dispersed defect-controlled carbon nanotube solution;

[0008] (3) preparing a SnO2 nanocrystal aqueous solution with a concentration of 0.1 to 1 mol / L;

[0009] (4) dissolving lead iodide in a mixed solution of DMF and DMSO with a volume ratio of 8 to 10:1 to a concentration of 1 to 2 mol / L;

[0010] (5) dissolving iodoformamidine, iodomethylamine and chloromethylamine in an isopropanol solution at a mass ratio of 10-30:1:1-2, and the total solute concentration is 0.5-1 mol / L;

[0011] (6) dissolving a p-type organic semiconductor material, LiTFSI, and TBP in the defect-controlled carbon nanotube solution in step (2) at a mass ratio of 6 to 10:1:0.001 to 0.005 to prepare a hole transport layer solution, wherein the concentration of the organic semiconductor material is 0.5 to 1.5 mol / L;

[0012] (7) dispersing graphene powder in isopropanol at a concentration of 0.3 to 2 g / L, and ball milling for 10 to 24 hours to obtain a uniformly dispersed graphene dispersion;

[0013] (8) Spin coating the SnO2 solution in step (3) on a FTO or ITO conductive glass substrate at a speed of about 2000 to 6000 rpm for 30 seconds, and then heating at 80 to 200° C. for 30 to 60 minutes;

[0014] (9) spin coating the lead iodide solution prepared in step (4) on the surface of the tin dioxide prepared in step (8) at a speed of 1500 rpm for 30 seconds, and then heating at 60 to 100° C. for 5 to 30 seconds;

[0015] (10) spin coating the solution prepared in step (5) on the surface of the film prepared in step (9) at a rotation speed of 2000 to 4000 rpm for 30 seconds, and then heating at 100 to 150° C. for 5 to 20 minutes;

[0016] (11) spin coating the hole transport layer solution prepared in step (6) on the surface of the film in step (10) at a speed of 1000 to 4000 rpm for 30 seconds;

[0017] (12) spraying the graphene dispersion prepared in step (7) onto the surface of the film in step (11) to a thickness of 0.5 to 10 μm to obtain a half-cell A;

[0018] (13) spraying the graphene dispersion prepared in step (7) onto a FTO or ITO conductive glass substrate with a thickness of 0.5 to 10 μm to obtain a half-cell B;

[0019] (14) The half cells A and B are packaged relative to each other to assemble into a carbon-based perovskite solar cell.

[0020] Furthermore, the carbon nanotubes in step (1) are any one or more of single-arm carbon nanotubes or multi-wall carbon nanotubes; and the concentration of the carbon nanotubes in the mixed solution is 2 to 3 g / L.

[0021] Furthermore, the other solvent in step (2) is any one of toluene, isopropanol, ether, and trifluorotoluene, or a combination of two or more thereof.

[0022] Furthermore, the preparation method of the SnO2 nanocrystal aqueous solution in step (3) is a sol-gel method.

[0023] Furthermore, in step (6), the p-type organic semiconductor is any one of hole transport materials for solar cells such as Poly(3-hexylthiophene-2,5-diyl)(P3HT), 2,2',7,7'-Tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene(Spiro-OMeTAD), Poly[bis(4-phenyl)(2,4,6-triMethylphenyl)aMine](PTAA), and Poly(3,4-ethylenedioxythiophene)(PEDOT).

[0024] Furthermore, the photoelectric conversion efficiency of the carbon-based perovskite solar cell can still maintain more than 95% of the original device efficiency after 800 hours of continuous illumination operation. The photoelectric conversion efficiency of the carbon-based perovskite solar cell is 20% to 23%, the open circuit voltage is 1.0 to 1.2V, and the short circuit current density is 24 to 27mA·cm -2 , the filling factor is 0.7~0.8.

[0025] Compared with the prior art, the advantages and technical effects of the present invention are as follows: the present invention provides a method for improving the performance of carbon-based perovskite solar cells, optimizes the electrical properties of CNTs by regulating the defect state density of CNTs, and uses defect-controlled CNTs to modify organic p-type semiconductors to prepare HTLs, thereby optimizing the energy level arrangement between HTL / graphene electrodes, which is beneficial to reducing energy loss. At the same time, the surface roughness of HTLs is increased by using the morphological characteristics of CNTs to improve the interface contact of HTL / graphene to achieve effective charge extraction. In addition, the high conductivity of CNTs provides a high-speed transmission channel for carrier transmission in HTLs. By optimizing the interface of HTL / carbon electrode, the carrier transmission process is accelerated, the spatial charge accumulation is reduced, the recombination reaction of carriers is reduced, the battery performance is significantly improved, and the efficiency of the current carbon-based perovskite solar cells is increased to more than 22%. The method for improving carbon-based perovskite solar cells of the present invention is simple, easy to operate, low-cost, and has a large room for improvement. More importantly, the battery has excellent stability and performance. The assembled carbon-based perovskite solar cell can still maintain the original efficiency of more than 95% after running for 800 hours under continuous illumination. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a scanning electron microscope photo of the defect-controlled small-sized CNT prepared in the present invention.

[0027] Figure 2 This is a transmission electron microscope photo of the defect-controlled small-sized CNT prepared by the present invention.

[0028] Figure 3 The cell efficiency curve of the perovskite solar cell prepared by the present invention before and after defect-regulated small-size CNT interface modification.

[0029] Figure 4 The stable performance of the continuous illumination test of the perovskite solar cell prepared by the present invention after defect regulation and small-size CNT interface modification. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is further described in detail below in conjunction with specific implementation methods.

[0031] Example 1

[0032] The method for improving the performance of a carbon-based perovskite solar cell according to the present invention comprises the following steps:

[0033] 1. Disperse 100 mg of carbon nanotubes in a mixed solution of 0.1 L of 98% concentrated nitric acid and 0.3 L of concentrated sulfuric acid, and then ultrasonically treat at 50°C for 12 hours; repeatedly wash the dispersion with deionized water until it is neutral, and dry the obtained solid under vacuum conditions for 48 hours to obtain a carbon nanotube powder with controlled defect state density;

[0034] 2. Disperse 10 mg of the above carbon nanotube powder in 0.3 L of chlorobenzene and ball mill for 20 hours to obtain a small-sized uniformly dispersed defect-controlled carbon nanotube solution;

[0035] 3. Prepare a SnO2 nanocrystal aqueous solution with a concentration of 0.5 mol / L;

[0036] 4. Dissolve 690 mg of lead iodide in a mixed solution of 900 μL DMF and 100 μL DMSO by volume;

[0037] 5. Dissolve 90 mg of iodoformamidine, 6.5 mg of iodomethylamine, and 9 mg of chloromethylamine in 1 mL of isopropanol solution;

[0038] 6. Dissolve 72 mg of 2,2′,7,7′-tetrakis(N,N-di-p-methoxyphenylamine)-9,9′-spirobifluorene(Spiro-OMeTAD), 9.1 mg of LiTFSI, and 0.03 mg of TBP in 1 mL of the defect-controlled carbon nanotube solution in step 2 to prepare a hole transport layer solution;

[0039] 7. Disperse 10 mg of graphene powder in 20 mL of isopropanol and ball mill for 20 hours to obtain a uniformly dispersed graphene dispersion;

[0040] 8. Spin coat the SnO2 solution in step 3 on the FTO conductive glass substrate at a speed of 3000 rpm for 30 seconds, and then heat at 150°C for 30 minutes;

[0041] 9. Spin-coat the lead iodide solution prepared in step 4 onto the surface of the tin dioxide prepared in step 8 at a speed of 1500 rpm for 30 seconds, and then heat at 70° C. for 20 seconds;

[0042] 10. Spin-coat the solution prepared in step 5 onto the surface of the film prepared in step 9 at a speed of 2000 rpm for 30 seconds, and then heat at 150° C. for 10 minutes;

[0043] 11. Spin-coat the hole transport layer solution prepared in step 6 onto the surface of the film in step 10 at a speed of 3000 rpm for 30 seconds;

[0044] 12. Spray the graphene dispersion prepared in step 7 onto the surface of the film in step 11 with a thickness of 2 μm to obtain half-cell A;

[0045] 13. Spray the graphene dispersion prepared in step 7 onto the FTO conductive glass substrate with a thickness of 2 μm to obtain a half-cell B;

[0046] 14. The half cells A and B are packaged relative to each other to assemble into a carbon-based perovskite solar cell.

[0047] By using the above method, an open circuit voltage of 1.0 to 1.2 V and a short circuit current of 24 to 27 mA cm can be obtained. -2 The carbon-based perovskite solar cell has a filling factor of 0.7 to 0.8, a photoelectric conversion efficiency of 20 to 23%, and no significant attenuation of the battery performance after continuous testing for 800 hours under continuous illumination. The carbon-based perovskite solar cell of the present invention can be used as a battery component and a power station.

[0048] Comparative Example 2

[0049] The method for improving the performance of a carbon-based perovskite solar cell according to the present invention comprises the following steps:

[0050] 1. Disperse 10 mg of carbon nanotube powder in 0.3 L of chlorobenzene and ball mill for 20 hours to obtain a small-sized and uniformly dispersed carbon nanotube solution;

[0051] 2. Prepare a SnO2 nanocrystal aqueous solution with a concentration of 0.5 mol / L;

[0052] 3. Dissolve 690 mg of lead iodide in a mixed solution of 900 μL DMF and 100 μL DMSO by volume;

[0053] 4. Dissolve 90 mg of iodoformamidine, 6.5 mg of iodomethylamine, and 9 mg of chloromethylamine in 1 mL of isopropanol solution;

[0054] 5. Dissolve 72 mg of 2,2′,7,7′-tetrakis(N,N-di-p-methoxyphenylamine)-9,9′-spirobifluorene(Spiro-OMeTAD), 9.1 mg of LiTFSI, and 0.03 mg of TBP in 1 mL of the carbon nanotube solution prepared in step 1 to prepare a hole transport layer solution;

[0055] 6. Disperse 10 mg of graphene powder in 20 mL of isopropanol and ball mill for 20 hours to obtain a uniformly dispersed graphene dispersion;

[0056] 7. Spin-coat the SnO2 solution in step 2 on the FTO conductive glass substrate: the speed is 3000 rpm, the time is 30 seconds, and then heat at 150°C for 30 minutes;

[0057] 8. Spin-coat the lead iodide solution prepared in step 3 onto the surface of the tin dioxide prepared in step 8 at a speed of 1500 rpm for 30 seconds, and then heat at 70° C. for 20 seconds;

[0058] 9. Spin-coat the solution prepared in step 4 onto the surface of the film in step 9 at a speed of 2000 rpm for 30 seconds, and then heat at 150° C. for 10 minutes;

[0059] 10. Spin-coat the hole transport layer solution prepared in step 5 onto the surface of the film in step 10 at a speed of 3000 rpm for 30 seconds;

[0060] 11. Spray the graphene dispersion prepared in step 6 onto the surface of the film in step 11 with a thickness of 2 μm to obtain half-cell A;

[0061] 12. Spray the graphene dispersion prepared in step 6 onto the FTO conductive glass substrate with a thickness of 2 μm to obtain a half-cell B;

[0062] 13. The half cells A and B are packaged relative to each other to assemble into a carbon-based perovskite solar cell.

[0063] By using the above method, an open circuit voltage of 0.9 to 1.0 V and a short circuit current of 24 to 25 mA cm can be obtained. -2, a carbon-based perovskite solar cell with a filling factor of 0.6 to 0.7 and a photoelectric conversion efficiency of 18 to 20%. Compared with the examples, it can be seen that in the comparative example, due to the lack of regulation of carbon nanotube defects, there are fewer oxygen-containing functional groups, and the electrostatic dipole interaction with Spiro-OMeTAD is weakened, which reduces the charge extraction and transfer properties at the molecular level, reduces the photocurrent and photovoltage, and the performance of the final C-PSC device.

[0064] Comparative Example 3

[0065] The method for improving the performance of a carbon-based perovskite solar cell according to the present invention comprises the following steps:

[0066] 1. Disperse 100 mg of carbon nanotubes in a mixed solution of 0.1 L of 98% concentrated nitric acid and 0.3 L of concentrated sulfuric acid, and then ultrasonically treat at 50°C for 12 hours; repeatedly wash the dispersion with deionized water until it is neutral, and dry the obtained solid under vacuum conditions for 48 hours to obtain a carbon nanotube powder with controlled defect state density;

[0067] 2. Prepare a SnO2 nanocrystal aqueous solution with a concentration of 0.5 mol / L;

[0068] 3. Dissolve 690 mg of lead iodide in a mixed solution of 900 μL DMF and 100 μL DMSO by volume;

[0069] 4. Dissolve 90 mg of iodoformamidine, 6.5 mg of iodomethylamine, and 9 mg of chloromethylamine in 1 mL of isopropanol solution;

[0070] 5. Disperse 72 mg of 2,2′,7,7′-tetrakis(N,N-di-p-methoxyphenylamine)-9,9′-spirobifluorene(Spiro-OMeTAD), 9.1 mg of LiTFSI, 0.03 mg of TBP and 5 mg of the carbon nanotubes prepared in step 1 in 1 mL of chlorobenzene to prepare a hole transport layer solution;

[0071] 6. Disperse 10 mg of graphene powder in 20 mL of isopropanol and ball mill for 20 hours to obtain a uniformly dispersed graphene dispersion;

[0072] 7. Spin-coat the SnO2 solution in step 2 on the FTO conductive glass substrate: the speed is 3000 rpm, the time is 30 seconds, and then heat at 150°C for 30 minutes;

[0073] 8. Spin-coat the lead iodide solution prepared in step 3 onto the surface of the tin dioxide prepared in step 8 at a speed of 1500 rpm for 30 seconds, and then heat at 70° C. for 20 seconds;

[0074] 9. Spin-coat the solution prepared in step 4 onto the surface of the film in step 9 at a speed of 2000 rpm for 30 seconds, and then heat at 150° C. for 10 minutes;

[0075] 10. Spin-coat the hole transport layer solution prepared in step 5 onto the surface of the film in step 10 at a speed of 3000 rpm for 30 seconds;

[0076] 11. Spray the graphene dispersion prepared in step 6 onto the surface of the film in step 11 with a thickness of 2 μm to obtain half-cell A;

[0077] 12. Spray the graphene dispersion prepared in step 6 onto the FTO conductive glass substrate with a thickness of 2 μm to obtain a half-cell B;

[0078] 13. The half cells A and B are packaged relative to each other to assemble into a carbon-based perovskite solar cell.

[0079] By using the above method, an open circuit voltage of 0.8 to 0.9 V and a short circuit current of 23 to 24 mA cm can be obtained. -2 , a carbon-based perovskite solar cell with a filling factor of 0.5 to 0.6 and a photoelectric conversion efficiency of 15 to 18%. Compared with the examples, it can be seen that in the comparative example, due to the lack of regulation of the size of defective carbon nanotubes, the larger-sized carbon nanotubes are compounded with Spiro-OMeTAD, which seriously reduces the film crystal quality and interface matching, resulting in a large number of recombination of photogenerated carriers, reducing the photovoltage and filling factor as well as the performance of the final C-PSC device.

[0080] Comparative Example 4

[0081] The method for improving the performance of a carbon-based perovskite solar cell according to the present invention comprises the following steps:

[0082] 1. Prepare a SnO2 nanocrystal aqueous solution with a concentration of 0.5 mol / L;

[0083] 2. Dissolve 690 mg of lead iodide in a mixed solution of 900 μL DMF and 100 μL DMSO by volume;

[0084] 3. Dissolve 90 mg of iodoformamidine, 6.5 mg of iodomethylamine, and 9 mg of chloromethylamine in 1 mL of isopropanol solution;

[0085] 4. Disperse 72 mg of 2,2′,7,7′-tetrakis(N,N-di-p-methoxyphenylamine)-9,9′-spirobifluorene(Spiro-OMeTAD), 9.1 mg of LiTFSI, 0.03 mg of TBP and 5 mg of untreated carbon nanotubes in 1 mL of chlorobenzene to prepare a hole transport layer solution;

[0086] 5. Disperse 10 mg of graphene powder in 20 mL of isopropanol and ball mill for 20 hours to obtain a uniformly dispersed graphene dispersion;

[0087] 6. Spin-coat the SnO2 solution in step 1 on the FTO conductive glass substrate: the rotation speed is 3000 rpm, the time is 30 seconds, and then heat at 150°C for 30 minutes;

[0088] 7. Spin-coat the lead iodide solution prepared in step 2 onto the surface of the tin dioxide prepared in step 6 at a speed of 1500 rpm for 30 seconds, and then heat at 70° C. for 20 seconds;

[0089] 8. Spin-coat the solution prepared in step 3 onto the surface of the film in step 7 at a speed of 2000 rpm for 30 seconds, and then heat at 150° C. for 10 minutes;

[0090] 9. Spin-coat the hole transport layer solution prepared in step 4 onto the surface of the film in step 8 at a speed of 3000 rpm for 30 seconds;

[0091] 10. Spray the graphene dispersion prepared in step 5 onto the surface of the film in step 9 with a thickness of 2 μm to obtain half-cell A;

[0092] 11. Spray the graphene dispersion prepared in step 5 onto the FTO conductive glass substrate with a thickness of 2 μm to obtain a half-cell B;

[0093] 12. The half cells A and B are packaged relative to each other to assemble into a carbon-based perovskite solar cell.

[0094] By using the above method, an open circuit voltage of 0.7 to 0.8 V and a short circuit current of 22 to 23 mA cm can be obtained. -2, a carbon-based perovskite solar cell with a filling factor of 0.4 to 0.5 and a photoelectric conversion efficiency of 12 to 15%. Compared with the examples, it can be seen that in the comparative example, due to the lack of regulation of carbon nanotube defects, there are fewer oxygen-containing functional groups, the electrostatic dipole interaction with Spiro-OMeTAD is weakened, and the charge extraction and transfer properties at the molecular level are reduced. At the same time, due to the lack of regulation of the size of defective carbon nanotubes, larger-sized carbon nanotubes reduce the crystallization quality of the film and the interface matching, resulting in a large number of recombination of photogenerated carriers, which seriously reduces the performance of the final C-PSC device.

[0095] Comparative Example 5

[0096] The method for improving the performance of a carbon-based perovskite solar cell according to the present invention comprises the following steps:

[0097] 1. Disperse 100 mg of carbon nanotubes in a mixed solution of 0.1 L of 98% concentrated nitric acid and 0.3 L of concentrated sulfuric acid, and then ultrasonically treat at 50°C for 12 hours; repeatedly wash the dispersion with deionized water until it is neutral, and dry the obtained solid under vacuum conditions for 48 hours to obtain a carbon nanotube powder with controlled defect state density;

[0098] 2. Disperse 10 mg of the above carbon nanotube powder in 0.3 L of chlorobenzene and ball mill for 20 hours to obtain a small-sized uniformly dispersed defect-controlled carbon nanotube solution;

[0099] 3. Prepare a SnO2 nanocrystal aqueous solution with a concentration of 0.5 mol / L;

[0100] 4. Dissolve 690 mg of lead iodide in a mixed solution of 900 μL DMF and 100 μL DMSO by volume;

[0101] 5. Dissolve 90 mg of iodoformamidine, 6.5 mg of iodomethylamine, and 9 mg of chloromethylamine in 1 mL of isopropanol solution;

[0102] 6. Dissolve 72 mg of 2,2′,7,7′-tetrakis(N,N-di-p-methoxyphenylamine)-9,9′-spirobifluorene(Spiro-OMeTAD), 9.1 mg of LiTFSI, and 0.03 mg of TBP in 1 mL of the defect-controlled carbon nanotube solution in step 2 to prepare a hole transport layer solution;

[0103] 7. Spin-coat the SnO2 solution in step 3 on the FTO conductive glass substrate: the speed is 3000 rpm, the time is 30 seconds, and then heat at 150°C for 30 minutes;

[0104] 8. Spin-coat the lead iodide solution prepared in step 4 onto the surface of the tin dioxide prepared in step 7 at a speed of 1500 rpm for 30 seconds, and then heat at 70° C. for 20 seconds;

[0105] 9. Spin-coat the solution prepared in step 5 onto the surface of the film in step 8 at a speed of 2000 rpm for 30 seconds, and then heat at 150° C. for 10 minutes;

[0106] 10. Spin-coat the hole transport layer solution prepared in step 6 onto the surface of the film in step 9 at a speed of 3000 rpm for 30 seconds;

[0107] 11. Spin-coat the small-size defect-controlled carbon nanotube dispersion prepared in step 2 onto the surface of the film in step 10 to obtain a carbon-based perovskite solar cell with CNTs serving as both HTL and counter electrode.

[0108] By the above method, the photoelectric conversion efficiency of the carbon-based perovskite solar cell obtained is 0-0.1%. Compared with the embodiment, it can be seen that the small-sized carbon nanotubes regulated by defects in the comparative example are small in size, making it difficult to form good lateral electron transmission, and are not suitable for the device structure as both the counter electrode and the HTL.

[0109] The above embodiments and comparative examples illustrate that, in the method for improving the performance of carbon-based perovskite solar cells described in the present invention, the processing of carbon nanotubes to form defect-controlled small-sized carbon nanotubes and doping them into HTL and applying them to a stacked carbon-based perovskite solar cell device structure in which two half-cells are relatively encapsulated is a key technical strategy for improving the performance of carbon-based perovskite solar cells. At the same time, the carbon nanotubes treated according to the method of the present invention are not suitable for a device structure that serves as both a counter electrode and a HTL.

[0110] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for a person skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to replace some of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions claimed to be protected by the present invention.

Claims

1. A method for improving the performance of carbon-based perovskite solar cells, characterized in that: The following steps are involved: (1) dispersing carbon nanotubes in a mixed solution of 98 wt.% concentrated nitric acid and 98 wt.% concentrated sulfuric acid in a volume ratio of 1:0.5-5, then ultrasonically treating the solution at 25-60° C. for 1-12 hours, repeatedly washing the dispersion with deionized water until it is neutral, and drying the obtained solid under vacuum conditions for 24-48 hours to obtain a carbon nanotube powder with controlled defect state density; (2) dispersing the carbon nanotube powder obtained in step (1) in chlorobenzene or other solvents at a concentration of 0.01 to 0.1 g / L, and ball milling for 10 to 24 hours to obtain a uniformly dispersed defect-controlled carbon nanotube solution; (3) preparing a SnO2 nanocrystal aqueous solution with a concentration of 0.1 to 1 mol / L; (4) dissolving lead iodide in a mixed solution of DMF and DMSO with a volume ratio of 8 to 10:1 to a concentration of 1 to 2 mol / L; (5) dissolving iodoformamidine, iodomethylamine and chloromethylamine in an isopropanol solution at a mass ratio of 10-30:1:1-2, and controlling the total solute concentration to be 0.5-1 mol / L; (6) dissolving a p-type organic semiconductor material, LiTFSI, and TBP in the defect-controlled carbon nanotube solution in step (2) at a mass ratio of 6 to 10:1:0.001 to 0.005 to prepare a hole transport layer solution, wherein the concentration of the organic semiconductor material is 0.5 to 1.5 mol / L; (7) dispersing graphene powder in isopropanol at a concentration of 0.3 to 2 g / L, and ball milling for 10 to 24 hours to obtain a uniformly dispersed graphene dispersion; (8) Spin coating the SnO2 nanocrystal aqueous solution in step (3) on a FTO or ITO conductive glass substrate at a speed of 2000 to 6000 rpm for 30 seconds, and then heating at 80 to 200° C. for 30 to 60 minutes; (9) spin coating the lead iodide solution prepared in step (4) on the surface of the tin dioxide prepared in step (8) at a rotation speed of 1500 rpm for 30 seconds, and then heating at 60 to 100° C. for 5 to 30 seconds; (10) spin coating the solution prepared in step (5) on the surface of the film prepared in step (9) at a rotation speed of 2000 to 4000 rpm for 30 seconds, and then heating at 100 to 150° C. for 5 to 20 minutes; (11) spin coating the hole transport layer solution prepared in step (6) on the surface of the film in step (10) at a speed of 1000 to 4000 rpm for 30 seconds; (12) spraying the graphene dispersion prepared in step (7) onto the surface of the film in step (11) to a thickness of 0.5 to 10 μm to obtain a half-cell A; (13) spraying the graphene dispersion prepared in step (7) onto a FTO or ITO conductive glass substrate with a thickness of 0.5 to 10 μm to obtain a half-cell B; (14) The half cells A and B are packaged relative to each other to assemble into a carbon-based perovskite solar cell.

2. A method for improving the performance of carbon-based perovskite solar cells according to claim 1, characterized in that: In step (1), the carbon nanotubes are single-walled carbon nanotubes and / or multi-walled carbon nanotubes, and their concentration in the mixed solution is 2-3 g / L.

3. A method for improving the performance of a carbon-based perovskite solar cell according to claim 1 or 2, characterized in that: The other solvent in step (2) is one or a mixture of two or more of toluene, isopropanol, ether and trifluorotoluene.

4. A method for improving the performance of a carbon-based perovskite solar cell according to claim 1 or 2, characterized in that: In step (6), the p-type organic semiconductor is Poly(3-hexylthiophene-2,5-diyl), 2,2',7,7'-Tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, Poly[bis(4-phenyl)(2,4,6-triMethylphenyl)aMine] or Poly(3,4-ethylenedioxythiophene).

5. A method for improving the performance of carbon-based perovskite solar cells according to claim 3, characterized in that: In step (6), the p-type organic semiconductor is Poly(3-hexylthiophene-2,5-diyl), 2,2',7,7'-Tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, Poly[bis(4-phenyl)(2,4,6-triMethylphenyl)aMine] or Poly(3,4-ethylenedioxythiophene).

Citation Information

Patent Citations

  • Novel solar cell device and preparation method thereof

    CN105355787A

  • Perovskite solar cell taking halogenated graphene oxide as additive and hole transport layer and preparation method thereof

    CN112420877A